Introduction to Nuclear Reactor Experiments - Wakabayashi, Genichiro; Yamada, Takahiro; Endo, Tomohiro; Pyeon, Cheol Ho (Springer Nature Singapore : Imprint: Springer, 2023)
This open access book is a pedagogical text on nuclear reactor experiments, covering almost all the experiments that can be carried out at the University Training Reactor, Kindai University (UTR-KINKI) with respect to reactor physics and radiation detection, and additionally including academic materials of test and research reactors, nuclear instrumentation, nuclear laws and regulations, in this main body. The book is an excellent primer for students who are interested in reactor physics, radiation detection, nuclear laws and regulations at universities, and the best textbook for students who have started to study the nuclear energy related fields to understand the basic theories and principles of the experiments in the fields of reactor physics and radiation detection. UTR-KINKI has been used for educational reactor experiments and basic research in a wide range of fields related to the use of radiation (neutrons, gamma-ray, beta-ray, alpha-ray, and X-ray), including reactor physics, radiation detection, radiation health physics, activation analysis, radiation biology, medical applications and archaeology. Also, UTR-KINKI has been actively engaged in nuclear education with its long history of operation, and has gained extensive experience in educational activities for undergraduate and graduate students, elementary, junior high and high school teachers, junior high and high school students, and general audiences.